2014
DOI: 10.1007/s12011-014-0015-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Extent of LINE-1 Mobility Following Exposure to Heavy Metals in HepG2 Cells

Abstract: The long interspersed elements-1 (LINE1 or L1 retrotransposon) constitute 17% of the human genome and retain mobility properties within the genome. At present, 80-100 human L1 elements are thought to be active in the genome. The mobilization of these active elements may be influenced upon exposure to the heavy metals. In the present study, we evaluated the association of aluminum, lead, and copper exposure with L1 retrotransposition in human hepatocellular carcinoma (HepG2) cell line. An in vitro retrotranspos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Not all types of heavy metals increase TE activity; an indication that the influence observed on TEs is unlikely the result of a generalized metal-induced stress response. LINE-1 retrotransposition increases when treated with mercury [90,91], arsenic trioxide [92], aluminum [93], cadmium [91,94] and nickel [95]. Zinc and magnesium can reverse the effects of cadmium- and nickel-driven increases in LINE-1 retrotransposition [94].…”
Section: The Influence Of Environmental Stimuli and Heavy Metals On Tmentioning
confidence: 99%
“…Not all types of heavy metals increase TE activity; an indication that the influence observed on TEs is unlikely the result of a generalized metal-induced stress response. LINE-1 retrotransposition increases when treated with mercury [90,91], arsenic trioxide [92], aluminum [93], cadmium [91,94] and nickel [95]. Zinc and magnesium can reverse the effects of cadmium- and nickel-driven increases in LINE-1 retrotransposition [94].…”
Section: The Influence Of Environmental Stimuli and Heavy Metals On Tmentioning
confidence: 99%
“…Previous reports have shown that some environmental factors like Gamma irradiation and X-rays some environmental triggers like benzo[a]pyrene (B[a]P), organochlorine pesticides, food-borne carcinogens, extremely low-frequency magnetic fields (ELF-MF) and some heavy metals like mercury, arsenic, aluminum increase L1 retrotransposition events [31][32][33]. Since the skin is the first line of defense for mentioned factors, so the higher expression of the level of ORF1 due to the exposure to agents is plausible.…”
Section: Discussionmentioning
confidence: 99%
“…Karimi et al . (Karimi et al ., ) evaluated the possible effect of copper on human L1 retrotransposition by using in vitro retrotransposition assays on HepG2 cells which were transfected with EGFP‐tagged L1 vector. They observed a decrease of percentage EGFP positive cells in samples treated with a dose of copper (Cu) of 50 μM or 75 μM as compared to control cells, and they confirmed this result evaluating the copy number of EGF gene inserted in the genome.…”
Section: Environmental Chemical Agents and Their Effect On L1‐rtpmentioning
confidence: 96%
“…Karimi et al . (Karimi et al ., ) evaluated the possible effect of aluminum on human L1 retrotransposition. In vitro retrotransposition assays were performed in human hepatocellular carcinoma cells (HepG2) transfected with EGFP‐tagged L1 vector.…”
Section: Environmental Chemical Agents and Their Effect On L1‐rtpmentioning
confidence: 99%
See 1 more Smart Citation